Antecedents of environmentally responsible behaviour in selected marine parks in Peninsular Malaysia - Mohammed, Nadzirah (2018)
Malaysia is one of the twelve megadiverse (or mega biodiversity) countries in the world and marine parks are part of the biodiversity components. The establishment of marine parks is to systematically protect and manage the marine ecosystem which can acknowledge Malaysia as a nature hub. However, tourism activities have adverse effects on the marine ecosystem. There were also negative reviews from the tourists on the landscape, services, and safety and security of the marine parks in Malaysia. Accordingly, positive environmental behaviour amongst the tourists plays a pivotal role in sustaining the success of marine parks. Addressing that, this study aimed to examine the influence of destination attractiveness, place attachment, activity involvement, and place satisfaction on environmentally responsible behaviour amongst tourists in marine parks. This study performed a questionnaire survey which involved on-site respondents in selected marine parks in Malaysia, namely Pulau Tioman, Pulau Redang, Pulau Perhentian, Pulau Payar, and Pulau Tinggi. A total of 388 completed surveys were used in the present study. Descriptive statistics were used to identify demographic profiles, travel profiles as well as descriptive frequencies and percentages for each item for each variable. Subsequently, this study utilised structural equation modelling (SEM) to examine the relationships between all the constructs with respect to the five proposed hypotheses. Conclusively, four of the proposed hypotheses (H1, H2, H4, and H5) were supported based on the obtained results of this study. However, the relationship between place attachment and place satisfaction (H3) was found to be negative in this study. Additionally, this study also found full mediation effects of place satisfaction towards the relationship between destination attractiveness and environmentally responsible behaviour. Concisely, this study conducted in-depth evaluation on the environmentally responsible behaviour amongs tourists in the marine parks. This study also took into account a comprehensive assessment on the three dimensions of destination attractiveness (core attributes, augmented attributes, and safety and security attributes) and the four dimensions of place attachment (place dependence, place identity, place affect, and place social bonding). The findings of this study also contribute to the sustainable planning on the development of marine parks in Malaysia.